Designing Context-Based Digital Comic Video for English for Specific Purposes (ESP) at Vocational High School Tourism Students - Anisa Pinkan Aulia; Ni Putu Artila Dewi; Isyarotullatifah; Kadek Lina Kurniawati (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aimed to design and develop a context-based digital comic video as an English for Specific Purposes (ESP) learning medium to enhance speaking skills among Grade 11 Tourism students at SMK TP 45 Negara, Jembrana, Bali. The research employed a Design and Development (D&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through needs analysis questionnaires, expert validation instruments, teacher response forms, and student practicality questionnaires. The developed media integrates ESP principles, Contextual-Based Learning (CBL), and local Jembrana tourism content. Validity assessment by two material experts yielded a combined score of 85.00% ("Valid, can be used with revision") with a Gregory’s content validity coefficient of 1.00 ("Very High Validity"). Media design validation by two media experts produced a combined average of 91.43% ("Very Valid"). Practicality evaluation by the English teacher resulted in 74.00% and by 31 students resulted in 80.26% ("Good"), giving a total practicality average of 77.13% ("Valid, can be used with revision"). These results confirm that the context-based digital comic video is valid, practical, and suitable for use in vocational tourism ESP classrooms.